Feminist Thoughts in the Works of Manikkodi B.S Ramiah - D, Palraj (International Research Journal of Tamil, 2022)
Literature is a reflection of human life. Sangam literature embodies all aspects of human life, from contemporary to modern literature. Modern literature such as novels, short stories, poetry, and drama evoke contemporary creators’ ideas of family, individual human life, feminism, class, and society through their works. The golden age of short story literature is manikkodi period. Manikkodi magazine started by ku. Srinivasan was transformed into a women’s short story magazine run by B.S Ramiah. Innovator, La.Sa.Ra., Va. Ra, Mauni, B.S Ramiah, etc. continued to write short stories in Manikkodi magazine. Bharathiyar, Bharathidasan and Puthumaipittan took feminist ideas with a sense of liberation through their works. Socially concerned B.S Ramiah realistically records the life and social problems of the middle class. The oppression of men on feminist issues, the emancipation of women and the means by which this society can break the restrictions imposed on them and claim their rights. Women become widows at a young age because they get married at a young age. Through his short stories, B.S Ramiah has highlighted the progressive thinking that widows can be remarried at a young age, highlighting the denial of remarriage to widows and the stigma attached to widows by this society.